EVALUASI KINERJA SIMPANG BERSINYAL PADA PERSIMPANGAN JALAN RADEN PANJI SUROSO-JALAN SUNANDAR PRIYO SUDARMO-JALAN LAKSDA ADI SUCIPTO KOTA MALANG - Achmad Rodiyan Alaik; Ibnu Sholichin; Aulia Dewi Fatikasari (Racic : Rab Construction Research, 2026)
Urban area growth has led to increased traffic volume, necessitating an evaluation of signalized intersection performance to maintain smooth transportation. This study aims to analyze the performance of the signalized intersection at Jalan Raden Panji Suroso–Jalan Sunandar Priyo Sudarmo–Jalan Laksda Adi Sucipto in Malang City, evaluate existing conditions, project traffic conditions for a 5-year planning horizon, and assess the effectiveness of intersection improvements. The method involved field surveys during morning and evening peak hours, processing traffic volume data in passenger car units (PCU), and analyzing capacity, degree of saturation, queue length, and delay according to the Indonesian Road Capacity Guidelines (PKJI 2023). The results show that the existing condition is at Level of Service (LOS) E with a degree of saturation (DS) of 0.87 and an average delay of 0.87 s/PCU. The 5-year projection without improvements remains at LOS E with DS 0.97. After implementing improvements, including road widening, additional traffic signs, heavy vehicle restrictions, and signal cycle optimization, the intersection performance improved to LOS C with DS 0.83–0.78 and average delay 0.73 s/PCU, indicating a more stable flow and reduced waiting time. This study provides a foundation for planning and upgrading intersections to enhance traffic performance